DETERMINASI TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Dinda Oktaviyanti; Ni Putu Eka Widiastuti; Satria Yudhia Wijaya (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
This study aims to determine the effect of income tax, tunneling incentive, and debt covenant on transfer pricing indications. The research population uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sampling technique was carried out by purposive sampling method. The study used 105 observational data. Logistic regression is a data analysis technique used in this study. The results of the study show that there is an effect of tunneling incentive, which is measured by the amount of foreign share ownership that exceeds 20% on transfer pricing. However, this study cannot prove the effect of income tax, as measured by the different box tax and debt covenants, as measured by the debt to equity ratio on transfer pricing.